An Experimental Study on Stern Slamming of a Ship with Steel Model (International Journal of Metacentre, 2022)
This study discusses the phenomenon of experimental-based slamming carried out on a towing tank using a piezo sensor placed on a 0.15 L plane measured from the AP. This research measures the pressure on the ship's hull and internal strain with a steel model. This study aims to determine the amount of pressure and distribution on the ship's hull and the internal strain that occurs. This study's results indicate that the value of internal stresses and strains increases with each increase in the aft angle given in the drop test. The greatest pressure occurs at sensor 2 in the bottom area, which first touches the water surface with an average increase in pressure of 23.89% and internal strain occurs at sensor 6 in the ivory construction at the stern of the ship with an average increase of 24.49% so that These areas need special attention in Typical frame section location for stren slamming and structure of the ship to minimize the damaging effects of the slamming phenomenon.